Türkiye’deki yabancı sermaye ve Alman yabancı sermayesinin Türk ekonomisindeki yeri - Talak, Kezban (My University, 1999)
Especiall, during last years, the movements of the foreign capital worth about $ 50 billions all over the world. In this total foreign capital the share of Turkey is 0.3 %. Our aim is to evaluate the role of German Foreign capital in Turkey, with the historical developments between our country and Germany. The migration to Germany since 1960s, the population existence of this migration in Germany and the investments in Germany are important. We tried to study in four parts. We studied the general foreign capital theory in the first part. We studied the foreign capital movements in Turkey and in the world in the second part. Meanwhile, we mentioned various laws and subjects here. So we touched on the legal side of the subject. In the third part we mentioned about the economical connections of Turkey and Germany. Because the economical process between Turkey and Germany makes the foundation of German foreign investments in Turkey. In the fourth part of our study, we tried to examine the place of direct German investments in Turkish economy. We evaluated our study seeing that German foreign investments in Turkey become dense on agriculture, cattle-dealing, employment, manufactured goods and mining. In addition, we mentioned in which places German foreign investments take place. A second addition is we mentioned about the adresses and activity spaces of German foreign investments in Turkey. The relations with OECD, NATO and customs union can give positive results for the side of investment guarantee. It can be said that German investments can be important advantages in Turkey because of the agreements with Germany. We can't say that, in spite of the past, the foreign capital is not being used in a correct way. It is known that there are different reasons of this. The most important reasons are these : The politicial stabilization, the economical stabilization, economical and politicial preferences and high inflation. In spite of these conditions, since 1980s, it can be said that it has seen a general improvement over the world in the foreign capital movements, a liberalisment trend in factors which prevents international investments. Because of this moderate climate, Türkey could get a good share from the world capital movements since 1980s. The most important factor in this subject is the decision which is taken in liberal economy and politics. Economic sources of the public companies have been made private by Turkish economy and the foreign capital investment companies have gained from this sitvation. Turkish economy has been living important economical negatives during last years. These are high inflation, inside debt, outside debt stock, budget. These are the negatives for the foreign capital. For German foreign investments we can say these thoughts. First of all,... hasn't got a completely matriculation in the economical, political, social period with Germany. German industrial goods have a very important credit in Turkish consumer market-place 20 % of the Turkish tourism belong to German investment companies. It can be said that, this is an affirmative improvement. In spite of this, German foreign investments in Turkey equal 1.1 % among the global outside investments of Germany. Positive cautions have to be taken to remove this situation. Especially, Turkey-Germany joint committee should be considered important; so the negatives which can occur should be removed. Between our country and Germany, for German foreign investments, we should benefit from Arbitration Law which is accepted in Turkish Parliament. Our country has got a very good climate for the foreign capital. German investment companies can put money in Turkish sections. German foreign capital investments make a large contribution to the Turkish economy as it has been mentioned above. If we appraise our study from this side, we can say this is a different alternative. People who defend foreign capital are in the side of free attemps and market machinery. The ones who are opposite of this defines government control on the economical activities. Foreign capital investments are useful for the country as lohg as the economical profits of host country and international company can be got along well.
Keywords: SERMAYE,ULUSLARARASI-TÜRKİYE